Study On Corporate And Customer Congruence In The Postulated Concept 'Strategic Integrated Positioning'. - Nair, Raghunath C.G. (2002)
A brand that is well positioned has a direct impact upon customer satisfaction and competitive advantage. Therefore, it is incumbent upon any organization to ensure that their efforts be directed towards implementing decisions that reduce customer attrition by getting and staying in the mind of customers. This study suggests that organization must implement the concept of 'Strategic Integrated Positioning'. The concept is a function of four elements -corporate image, brand value, service quality and people quality.